La psicomotricidad en la generación de aprendizajes de los niños de edad preescolar del centro ecuatoriano de audición y lenguaje de la ciudad de Loja, año. Lectivo 2011 – 2012. Lineamientos alternativos - Torres Valdivieso, Isabel Karina (2012)
The objective of this research was to establish how the psychomotor allows the generation of learning in preschool children of the The objective of this research was to establish how the psychomotor allows the generation of learning in preschool children of the Ecuadorian Center for Hearing and Language (CEAL). The methods used for processing were the descriptive method, empirical, scientific and deductive-inductive method, and applied the techniques and instruments: a survey of teachers and parents, as well as a test to children who assist the Ecuadorian Center for Hearing and Language of the City of Loja that enabled them to optimize this research work, whose main function was to describe reality, taking into account the variables and indicators that were investigated and helped to improve the issues raised . Tabulated data of the instruments we obtain the following results: The data provided by teachers and parents concluded with 85% to the development of gross and fine motor skills contribute to the generation of cognitive learning, procedural and attitudes in preschool children of the Ecuadorian Center for Hearing and language. In relation to data provided by the application of the test to children is concluded that 48% of preschool children in the Ecuadorian Center for Hearing and Speech, lack of dynamic and static body control, determine slowness, visuo motor incoordination , balance and rhythm down. While 52% of manual eye coordination and motor phonetics, facial gestures and preschool children of the Ecuadorian Center for Hearing and Speech, does not allow cognitive learning, procedural and attitudinal literacy. Importantly, the motor skills is a result that involves not only sensory structures, motor and intellectual, but also the processes that coordinate and gradually sorted the results of these structures, allowing the child a confidence and security in itself, since you will notice the domain that has your body in any situation.